2008
DOI: 10.1177/1557085107308456
|View full text |Cite
|
Sign up to set email alerts
|

Women and Crime in Context

Abstract: This study explores the relationship between patriarchy indicators and female offending in the context of urban and rural areas. Few studies have examined how patriarchy and other structural predictors influence within-gender differences in female crime at the macro level. Using 2000 data, the authors offer multiple measures that tap public and private levels of patriarchy when examining types of female arrests across U.S. cities and small towns. The authors find that public patriarchy influences female crime … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(9 citation statements)
references
References 68 publications
1
7
0
1
Order By: Relevance
“…The Hispanic Immigration Index is consistent with previous macro-level research on homicide (Ousey & Kubrin, 2018) and may be especially relevant for our examination of rural/urban differences given research that has established immigration into certain areas (e.g., sanctuary cities) serves as a protective factor against violence (Harris & Feldmeyer, 2013;Ousey & Kubrin, 2018;Shihadeh & Barranco, 2010). This same protective factor may not exist in rural communities, but nonetheless, the Hispanic population in the U.S. has grown substantially in recent decades, especially in rural areas (Parker & Reckdenwald, 2008). As with the Economic Disadvantage Index, the Hispanic Immigration Index was created using weighted factor loadings and had an Eigenvalue of 1.18.…”
Section: Control Variablessupporting
confidence: 80%
See 1 more Smart Citation
“…The Hispanic Immigration Index is consistent with previous macro-level research on homicide (Ousey & Kubrin, 2018) and may be especially relevant for our examination of rural/urban differences given research that has established immigration into certain areas (e.g., sanctuary cities) serves as a protective factor against violence (Harris & Feldmeyer, 2013;Ousey & Kubrin, 2018;Shihadeh & Barranco, 2010). This same protective factor may not exist in rural communities, but nonetheless, the Hispanic population in the U.S. has grown substantially in recent decades, especially in rural areas (Parker & Reckdenwald, 2008). As with the Economic Disadvantage Index, the Hispanic Immigration Index was created using weighted factor loadings and had an Eigenvalue of 1.18.…”
Section: Control Variablessupporting
confidence: 80%
“…Table 2 and Appendix A note the total number of counties with zero intimate femicides for each of our dependent variables and samples. There is no agreed upon way to define or operationalize the rural-urban divide (Annan, 2008;Parker & Reckdenwald, 2008). While a variety of operationalizations have been used in the literature, after conducting a systematic review of 50 studies on IPV in rural areas, Annan (2008) noted "Many of the rural IPV studies reviewed defined rural using the U.S. Census Data" (p. 90).…”
Section: Data and Samplementioning
confidence: 99%
“…CFAs supported both an oblique three-factor structure and a bifactor structure, justifying the use of both factor and total scale scores, respectively. Consis tent with the literature that highlighted multidimensionality of patriarchy, the PBS reflected patriarchal beliefs at micro-, meso-, and macrolevels of social systems, across politics, business, fi nance, religion, education, and domestic life (see Belknap, 2007;Clarricoates, 1981;Deutchman, 1998;Hartmann, 1976;MacKin non, 1989;Messerschmidt, 1986;Millett, 1969;Parker & Reckdenwald, 2008). Construct validity of the PBS was further sup ported in relation to modem sexism, antifeminist attitudes, and egalitarian attitudes toward women.…”
Section: Discussionmentioning
confidence: 97%
“…However, it is noticeable that the imprisonment rate of rural women for both assaults and homicide-a crime unlikely to be subject to selective policing-was higher than the general imprisonment of rural women (but still under-represented compared to the overall female population). More contemporary studies have found that women's violence is strongly driven by IJCJ&SD 108 Online version via www.crimejusticejournal.com © 2019 8(1) rates of male violence in rural environments (Parker and Reckdenwald 2008). Some of the factors suggested by recent scholarship as contributing to violence in modern rural areas-such as isolation, heavy-drinking cultures and more limited access to support services-are likely to have also been relevant historically (Hogg and Carrington 2006: 65;Jobes et al 2001).…”
Section: Offence Profiles Of Female Prisoners In Urban and Rural Victmentioning
confidence: 99%